Tantangan Manajemen Sumber Daya Manusia Dalam Mengelola Karyawan Generasi Z Di Tempat Kerja - Tri Aslikhah, Ulfatin; Dwi Erianti, Anggi; Nur Agitama, Vidya (J-LEE - Journal of Law, English, and Economics, 2025)
Abstract The development of the digital era has brought significant changes in the dynamics of the world of work, one of which is the presence of Generation Z. This generation is known for its unique characteristics such as high ability to use technology, desire for work flexibility, and need for work-life balance. This research aims to examine the challenges faced by human resource management (HRM) in managing Generation Z employees in the workplace. The method used is a literature study with a qualitative descriptive approach based on relevant scientific sources. The results of the study show that Generation Z has high expectations for career development, rewards, and an adaptive and modern work environment. The main challenges faced by HRM include the need for work flexibility, digital communication styles, dependence on technology, and the demand for interactive and digital-based training.